Pengaruh Tunjangan Kinerja terhadap Kinerja Pegawai Dinas Lingkungan Hidup Kota Sorong - Elizabeth Rande; Wisnu Winata; Oktaviani Way; Andi Irwan (Jurnal Online Manajemen ELPEI, 2026)
The formulation of the problem raised in this title is how performance allowances influence employee performance in the Sorong City Environmental Service. The above problem is solved by gathering data from various subjects using the populist and statistical methods, as well as a study tool based on observation and consensus. Research can also be carried out according to predetermined procedures using administrative working hours and the above grid. Results of the Study Summarized in the First and Second Benefits with Positive Significance for Employee Performance with a Minimum of Around 0.767.